The Influence of Using Virtual Reality-Based Learning Media on Increasing Learning Motivation, Practical Skills, and Learning Outcomes of Jayapura Aviation Polytechnic Students - Pipa Biringkanae; Rifqi Raza Bunahri (Dinasti Publisher, 2024)
This study evaluates the influence of learning motivation, practical skills, and learning outcomes on the use of Virtual Reality (VR) learning media. The method used is ex-post facto with a quantitative correlation approach on 30 student samples using questionnaires and analysis through multiple linear regression. The results of the analysis show that learning motivation contributes significantly to the use of VR media, confirming the importance of motivation in maximizing the benefits of this technology in education. In contrast, practical skills have a negative but insignificant influence, indicating that this factor does not significantly affect the use of VR media in this context. Learning outcomes are proven to have a positive and significant influence, indicating that good learning achievement encourages the effective use of VR media. These findings emphasize the need to focus on motivation and learning outcomes in implementing VR technology to improve the quality of education.